(Ex)change of routines: An action-based microfoundation - Peter Kesting (Schmalenbach Journal of Business Research (SBUR), 2023)
Change necessitates companies to alter their established routines. But how flexible are routines, and how can they be changed? Research has given very different answers to this question. While some researchers see routines as rigid and opposed to change, others see them as flexible and a source of change. The problem is not only that these positions are unrelated, but that there is no foundation that conceptually encompasses and connects both elements of routines, rigidity and changeability, which is why these two facets currently present as opposites. Current research tends towards the second position, neglecting the rigidity of routines. This paper offers an action-based microfoundation of routine change expanding Feldman and Pentland's ostensive-performative approach beyond feedback processes. The focus of the theoretical conceptualization of routines is on action-specific knowledge acquired and applied through repetition. This action-based microfoundation allows the contradictory views of previous research to be positioned in a larger context. Routines are flexible, but only incrementally; they exhibit rigidity towards radical change. Building on this theoretical conceptualization, this paper distinguishes four types of routine changes: routinization/expansion, adaptation, problem fixing, and deliberate routine exchange. This distinction can contribute significantly to the focus of research and thus make it more rigorous. It also allows the rigidities of routines to be taken into account more strongly than before, thereby significantly increasing the relevance of routine research.
Keywords: D01; O12; O31; M20; 650; Routine; Micro foundation; Action; Inflexibility; Inertia